A2VB3VI crystals with tetradymite structure - Navrátil, Jiří; Starý, Zdeněk; Plecháček, Tomáš; Horák, Jaromír; Lošťák, Petr (Univerzita Pardubice, 1996)
The recent studies of layered thermoelectric materials of A2B3-tetradymite type compounds carried out by JLSSC and Department of Inorganic Chemistry of University of Pardubice are reviewed. The influents of some dopants (III.B–VI.B group) on transport (Seebeck coefficient, Hall constant, electrical conductivity) and optical properties (reflectance and transmittance in IR region) has been observed. From changes of these properties and with the help of quantum-chemical calculations, the view on the point defect nature has been obtained. These results have been applied to polycrystalline materials, too, with regard to the thermoelectric figure of merit.